2008
DOI: 10.1021/es800120b
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Oxidation of Methane: Mechanisms, Bioenergetics, and the Ecology of Associated Microorganisms

Abstract: Microbially mediated anaerobic oxidation of methane (AOM) moderates the input of methane, an important greenhouse gas, to the atmosphere by consuming methane produced in various marine, terrestrial, and subsurface environments. AOM coupled to sulfate reduction has been most extensively studied because of the abundance of sulfate in marine systems, but electron acceptors otherthan sulfate are more energetically favorable. Phylogenetic trees based on 16S rRNA gene clone libraries derived from microbial communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(119 citation statements)
references
References 95 publications
6
108
0
2
Order By: Relevance
“…AroB family of methanogens has phylogenetically corresponded with sulfur utilizing archaea as a result of sulfur cycling and methanogenesis are primarily drive microbial colonization (Borin et al 2009). Hence, it revealed the phylogenetic and metabolic relatedness for heavy metal assimilation pathways can likely be established among methanogens, sulfur utilizing archaea and methylotrophs, which is agreed with earlier works (Boetius et al 2000;Thomsen et al 2001;Orphan et al 2001Orphan et al , 2003Teske et al 2003;Caldwell et al 2008). Nonetheless, in silico representation should couple with an experimental program that may provide valuable information including genetic and metabolic regulatory systems of methanogens.…”
Section: Discussionsupporting
confidence: 84%
“…AroB family of methanogens has phylogenetically corresponded with sulfur utilizing archaea as a result of sulfur cycling and methanogenesis are primarily drive microbial colonization (Borin et al 2009). Hence, it revealed the phylogenetic and metabolic relatedness for heavy metal assimilation pathways can likely be established among methanogens, sulfur utilizing archaea and methylotrophs, which is agreed with earlier works (Boetius et al 2000;Thomsen et al 2001;Orphan et al 2001Orphan et al , 2003Teske et al 2003;Caldwell et al 2008). Nonetheless, in silico representation should couple with an experimental program that may provide valuable information including genetic and metabolic regulatory systems of methanogens.…”
Section: Discussionsupporting
confidence: 84%
“…AOM is a globally important biological process as it influences the emission of this potential greenhouse gas into the hydrosphere (Knittel et al, 2005). Although the mechanisms of AOM metabolism are not fully understood, AOM is believed to occur through either reverse methanogenesis (Hallam et al, 2004;Caldwell et al, 2008), a type of acetogenesis (Valentine and Reeburgh, 2000;Caldwell et al, 2008) or methylogenesis (Caldwell et al, 2008;Moran et al, 2008). It has been shown that ANME cells (including ANME-1) form consortia with SRB cells to couple AOM with sulfate reduction (Valentine and Reeburgh, 2000;Orphan et al, 2002) and very recently it has been shown that AOM can also be coupled to denitrification (Raghoebarsing et al, 2006) or to the use of manganese and iron oxidants (Beal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Methane-induced acetogenesis and sulphate reduction AOM is suggested to proceed via several pathways with a range of final electron acceptors (Caldwell et al, 2008). Some of these pathways include the formation of acetate from methane (Valentine and Reeburgh, 2000).…”
Section: Cell Density Control By Bacteriophagesmentioning
confidence: 99%